2014
DOI: 10.1111/brv.12147
|View full text |Cite
|
Sign up to set email alerts
|

Do hormone‐modulating chemicals impact on reproduction and development of wild amphibians?

Abstract: Globally, amphibians are undergoing a precipitous decline. At the last estimate in 2004, 32% of the approximately 6000 species were threatened with extinction and 43% were experiencing significant declines. These declines have been linked with a wide range of environmental pressures from habitat loss to climate change, disease and pollution. This review evaluates the evidence that endocrine-disrupting contaminants (EDCs) -pollutants that affect hormone systems -are impacting on wild amphibians and contributing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 157 publications
(236 reference statements)
1
73
0
2
Order By: Relevance
“…Hormonal manipulation and exposure to exogenous chemicals can cause sex reversal in amphibians with sex chromosomes [Dournon et al, 1990;Orton and Tyler, 2015], and similar manipulations have been conducted with TSD reptiles [Bull et al, 1988;Belaid et al, 2001;Warner and Shine, 2008;Mizoguchi and Valenzuela, 2016] reversing sex from that expected given the temperature of incubation. However, the relevance of these studies to what happens in the wild remains the subject of some conjecture.…”
Section: Definitive Cases Of Environmental Sex Reversal In Wild Reptimentioning
confidence: 99%
“…Hormonal manipulation and exposure to exogenous chemicals can cause sex reversal in amphibians with sex chromosomes [Dournon et al, 1990;Orton and Tyler, 2015], and similar manipulations have been conducted with TSD reptiles [Bull et al, 1988;Belaid et al, 2001;Warner and Shine, 2008;Mizoguchi and Valenzuela, 2016] reversing sex from that expected given the temperature of incubation. However, the relevance of these studies to what happens in the wild remains the subject of some conjecture.…”
Section: Definitive Cases Of Environmental Sex Reversal In Wild Reptimentioning
confidence: 99%
“…However, in lizards (17,18), fish (21), and some amphibians (22), temperature elevation tends to induce male development and male-biased sex ratios can dramatically reduce population fitness (23,24). Sexual differentiation in these animals is also strongly influenced by chemicals that disrupt hormone systems (25)(26)(27)(28). Some endocrine disrupting chemicals (EDCs) are highly potent pollutants, and exposure concentrations occurring in natural surface waters have been shown to affect reproductive development negatively in reptiles (29), amphibians (28), and fish (30,31).…”
mentioning
confidence: 99%
“…Sexual differentiation in these animals is also strongly influenced by chemicals that disrupt hormone systems (25)(26)(27)(28). Some endocrine disrupting chemicals (EDCs) are highly potent pollutants, and exposure concentrations occurring in natural surface waters have been shown to affect reproductive development negatively in reptiles (29), amphibians (28), and fish (30,31).…”
mentioning
confidence: 99%
“…Due to their highly permeable skin and, in most species, aquatic larval phase, dissolved chemicals can easily enter the body of amphibians and impair their somatic and sexual development by interference with the organisms' hormonal control. In addition, most amphibians are terrestrial as adults, and are thus also potential recipients of EDCs found in the terrestrial environment (Bhandari et al, 2015;Kloas, 2002;Orton and Tyler, 2014). Several studies testing effects of BPA on the somatic development of amphibians have been conducted and multiple negative outcomes were observed.…”
Section: Introductionmentioning
confidence: 99%